The effects of long-acting β2-agonists plus inhaled corticosteroids for early reversibility in patients with airway obstruction - Ozkaya, Sevket; Dirican, Adem; Tuna, Tibel (Journal of Thoracic Disease; Vol 5, No 4 (August 30, 2013): Journal of Thoracic Disease, 2013)
Background: Salbutamol, as a short-acting β2-agonist, was popularly used in the past for detection of reversibility in patients with airway obstruction when it was the only drug available in the treatment of airway obstruction. Today, the combination of long-acting β2-agonists (LABA) and inhaled glucocorticoids are the first choice of therapy, with or without the presence of reversibility, in patients with airway obstruction. We aimed to compare the efficacy of salbutamol and long acting β2-agonists plus inhaled glucocorticoids for early reversibility test in patients with airway obstruction. Methods: Symptomatic patients (cough, dyspnea, and/or wheezing) with airway obstruction according to pulmonary function testing (FEV1/FVC value less than 70% of expected) who had never used bronchodilators before or had not received short- or long-acting inhaled bronchodilator therapy within the most recent 12 hours were evaluated. Reversibility measurements were made by administering the combination of long-acting β2-agonists (LABA) and inhaled glucocorticoids after 15 minutes. Results: A total of 90 patients were evaluated. The mean age of patients was 57.3±17.7 (range: 8-88) years and the male-to-female ratio was 69/21. The baseline pulmonary function test results were mean FVC; 2,747±1,181 mL and 74.7%±21.4%, mean FEV1; 1,716±825 mL and 57.5%±19.0%, mean FEV1/FVC; 61.4%±7.4%. The bronchodilator drugs given before reversibility testing were as salmeterol/fluticasone (FTC/SAL), formoterol/budesonide (BUD/FOR), beclomethasone dipropionate/formoterol (BDP/FOR) and salbutamol (SLB) in 24, 22, 24 and 20 patients, respectively. The reversibility was positive in 33 (36.7%) patients. The absolute change and percentage of change in mean FEV1 were 206±252 mL, 13.2%±16.6% for FTC/SAL group, 273±201 mL, 14%±8% for BUD/FOR group, 240±151 mL, 18.7%±15.9% for BUD/FOR groupand 171±116 mL, 13.3%±11.8% for SLB group. There was no statistically significant for reversibilty results between LABAs/inhaledsteroids and SLB group. And the patients with positivere versibility test were significantly higher in both of BUD/FOR and BDP/FOR groups than SLB group. Conclusions: We think that performance of an early reversibility test using the combination of a LABA and an inhaled corticosteroid for treatment would enhance both the education of the patient in using the device and the reliability of the drug. And, we suggest that: “you should make the reversibility test with Long-Acting β2-Agonists plus Inhaled Corticosteroids which used in treatment of obstructive lung diseases”.